Analysis of Mathematics Learning of Students with Disabilities at Catur Bina Bangsa Extraordinary Elementary School - Andree Tiono Kurniawan; Masrurotul Mahmudah; Sudirin; Ummu Labibatus Sa’adah (Journal of Childhood Development, 2024)
This study discusses mathematics learning for mild mentally retarded students with an IQ of 68-52. Because in the learning process academic abilities are below average so that not all students can learn mathematical concepts well, it has implications for low student learning outcomes, Aims to find out the organization of material, implementation of learning strategies, obstacles, and student responses in (SDLB) Chess Nation Building. This research is a type of qualitative field research, namely a field research procedure that produces descriptive data. The results of this study are mostly from the aspect of organizing mathematics learning materials that have been implemented, the obstacles experienced by teachers during learning include mentally retarded children who are very hyperactive and do not want to continue learning and the response of mentally retarded students during positive learning.